A Design-Based Professional Development Module for Enhancing Mathematics Teachers’ Calculus Instruction Using GeoGebra - Bernard Justus Wekullo (Scientia Publica Media, 2026)
This is a three-week professional growth module for secondary mathematics teachers. The treatment aims to strengthen teachers’ ability to teach definite and indefinite integrals by integrating GeoGebra into calculus instruction. Informed by design-based research (DBR) principles, the professional growth module is conceptualized as an evolving instructional system that is refined through repeated implementation, analysis, and redesign, aligning theory, instructional design, and real-world practice. The module draws on constructivist principles, emphasizing learning through interaction, interpretation, and reflection. The instructional design is based on the Technological Pedagogical Content Knowledge (TPACK) framework, highlighting the coordinated integration of disciplinary knowledge, instructional strategies, and digital tools. The module is structured into three scaffolded phases, with Week One dedicated to strengthening teachers’ conceptual understanding of integration, particularly the ideas of accumulation and the area under a curve. Week Two emphasizes the development of digital literacy and symbolic skills by engaging teachers in structured GeoGebra explorations, where they dynamically model calculus concepts and connect algebraic, graphical, and numerical representations. Week Three targets instructional competence, requiring participants to design lesson plans, deliver mock teaching sessions with GeoGebra, provide peer feedback, and reflect on their pedagogical approaches. To capture changes in teachers’ conceptual understanding, digital literacy, and teaching approaches, data will be generated through pre- and post-Evaluations, reflective surveys, observations, and teaching and learning artifacts. Rather than treating the professional growth module as a static treatment, this study adopts an iterative design-based perspective that allows continuous refinement of both instructional activities and Evaluation tools. By examining teachers’ learning across conceptual, technological, and pedagogical dimensions, the study contributes a replicable model for a blended professional growth module for teaching calculus in secondary schools.